The impact of social media usage on small and micro social commerce enterprises in Malaysia - Shahizan Hassan; Arfan Shahzad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Due to the Covid-19 pandemic and movement control order (MCO), many small and micro-sized enterprises in Malaysia have been relying on social media platforms to promote and sell their products. Nonetheless, only a few studies were conducted on the success of this practice. The question of whether social media can indeed have an impact on social commerce performance remains unanswered. This study used mediating variables of social media in the relationship among ease of use, satisfaction, trust, perceived usefulness, social commerce performance, and the direct effect of social media use on social commerce performance among small and micro-enterprises in Malaysia. The data were collected from 100 business owners / managers of Malaysian small and microenterprises using social media for business. The study uses SPSS and PLS-SEM (partial least square based structural equation modeling) software for the data analysis. The results show that perceived usefulness, ease of use, satisfaction, and trust significantly impact social media use. The result also show that social media use positively impacts social commerce performance. This study consequently suggests that small and micro-enterprise owners / managers in Malaysia should effectively use social media to increase the scommerce performance for sustainable growth. They should fully utilize the popularity of the use of social media by providing useful and reliable information about their products or services to boost trust among potential buyers.
Keywords: 330; perceived usefulness; ease of use; satisfaction; trust; small and micro-enterprises social media use; social commerce enterprises